Early dynamic behavior of lactate in predicting continuous renal replacement therapy after surgery for acute type A aortic dissection - Wang, Zhigang; Xu, Jingfang; Kang, Yubei; Liu, Ling; Zhang, Lifang; Wang, Dongjin (Frontiers in Cardiovascular Medicine, 2022)
Background: It has been well known that hyperlactatemia is an independent risk factor for postoperative mortality in patients who received acute type A aortic dissection (ATAAD) surgery. Some patients may require the assistance of continuous renal replacement therapy (CRRT) for acute postoperative renal deficiency and often associate with increased mortality rate. This study aimed to examine the association between the early dynamic change of lactate levels and postoperative CRRT in ATAAD patients who received surgical repairment. Methods: This retrospective study included 503 patients who received ATAAD surgeries. Serum lactate levels were measured before operation and at 0, 1, 3, 6, 12, 24 hours post intensive care unit (ICU) admission. We examined the association between dynamic changes of lactate and CRRT. Results: Among all patients, 19.9% (100 patients) required CRRT. Our data showed that the lactate levels were higher in the CRRT group at all timepoints compared to the non-CRRT group. In a multivariate model, lactate levels at 12 hours post ICU admission [odds ratio (OR), 1.362; p = 0.007] was identified as an independent predictor for requiring CRRT. Unsurprisingly, 30-day mortality in the CRRT group (41%) was 8.2 times higher than in the non-CRRT group (5%). To better understand the associations between CRRT and lactate levels, patients in the CRRT group were further stratified into the non-survivor group (n = 41) and survivor group (n = 59) based on the 30-day mortality. Elevated lactate levels measured upon ICU admission (OR, 1.284; p = 0.001) and decreased 24 hours lactate clearance (OR, 0.237; p = 0.039) were independent risk factors for 30-day mortality in patients who received CRRT. The area under the curve to predict requirement for CRRT at 6 hours and 12 hours post CICU admission were 0.714 and 0.722, respectively, corresponding to lactate cut-off levels of 4.15 mmol/L and 2.45 mmol/L. Conclusion: The CRRT is commonly required in patients who received ATAAD surgery and often associated with worse mortality. Early dynamic changes of lactate levels can be used to predict the requirement of postoperative CRRT.